Between regional development and Integrated Coastal Zone Management. What future is there for the coastlines of Sub-Saharan Africa? - (:unkn) unknown (My University, 2010)
The ever expanding settlement of a large part of the Sub-Saharan coastlines is linked to the tremendous development of urban centers and of smaller local communities which depend on a variety of economic activities more or less associated with maritime life and trade. This has in turn given rise to an ever increasing number of conflicts over land use motivated by environmental or cultural interests at a time when mounting sea levels threaten the ways of life of the populations concerned. In the special context of Sub-Saharan Africa, Integrated Coastal Zone Management techniques, which associate all the parties concerned, seem better suited to areas in which anthropic pressure is limited while, in extreme situations, governments will have to handle the development of sprouting neighborhoods and to control hazardous industrial zones.
Keywords: African Research